The Impact of Institutional Excellence on Social Development in the United Arab Emirates: An Analytical Study - Radhi, Alya Ahmad; Hamdi, Wafa Barhoumi (Al-Adab Journal, 2023)
The purpose of this research is to determine how much institutional quality has contributed to the UAE’s socioeconomic success. The descriptive-analytical methodology was used to handle the study’s issue. The descriptive method was utilized to understand the concepts of institutional excellence and social development, as well as to establish their relationships and interdependence. The analysis methods was also employed to analyze the features of institutional excellence and their influence on social development by analyzing UAE tendencies. This analysis established that His Highness was the driving factor behind the UAE’s 28-year march to greatness. The Dubai Quality Award was established in 1994 by Sheikh Mohammed bin Rashid Al Maktoum, Vice President and Prime Minister of the United Arab Emirates and Ruler of Dubai, "may God protect him," to encourage the adoption of an excellence culture as a foundation for the growth of government activities. Following that, local excellence and quality programs were launched, culminating in the Sheikh Khalifa Government Excellence Program’s establishment in 2009. The term institutional excellence refers to a level of administrative and organizational innovation that results in major achievements and successes that satisfy customers and work to promote social development in all of its aspects in the UAE. The researchers recommended, based on the research data and findings, that the training plans and programs that have been implemented in government institutions in the UAE be reviewed to ensure their effectiveness and compatibility with the needs and requirements of government work and sustainable social development in the UAE.